Embedded Markets: A Dialogue between F.A. Hayek and Karl Polanyi - Migone, Andrea (Review of Austrian Economics, 2011)
The recent economic crisis has once more underscored the close connection between markets and social life, thrusting this point at the centre of the analysis of economic and political activity and has once more asked the question of whether and how individuals are embedded in both. Here I argue that an analysis and partial reconciliation of the positions of F. A. Hayek and Karl Polanyi on the topic can help in this debate.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; capitalist systems; embedded markets; history of economic thought

KARL POLANYI'S METACRITIQUE OF THE LIBERAL CREED Reading Polanyi's Social Theory in Terms of Dialectical Critical Realism - Despain, Hans G. (Journal of Critical Realism, 2011)
This paper interprets Karl Polanyi through dialectical critical realism. The paper maintains that this interpretation offers Polanyi methodological coherence and philosophical support. It further provides dialectical critical realism with an exemplar of explanatory critique. It is argued that the social theory of Polanyi aims at the demystification of market-systems as they are theoretically constructed by both orthodox and heterodox accounts of capitalism. Dialectical critical realism is best capable of situating the theoretical accomplishment of Polanyi's historical and dialectical critiques of social being.
Keywords: capitalism; critical realism; economic theory; economics; explanatory critique; liberal creed; neoliberalism; ontology; social history; social theory

Karl Polanyi: The Limits of the Market - Barnes, Tom (Journal of Australian Political Economy, 2011)
The article reviews the book "Karl Polanyi: The Limits of the Market," by Gareth Dale.
Keywords: DALE, Gareth; KARL Polanyi: The Limits of the Market (Book); Polanyi, Karl, 1886-1964

Would You Barter with God? Why Holy Debts and Not Profane Markets Created Money - Semenova, Alla (American Journal of Economics and Sociology, 2011)
Attempting to revitalize the substantive approach to economics in the tradition of K. Polanyi, this paper revives the neglected substantive theory of money's origins by Bernhard Laum and thus disputes the formal approaches that see the origins of money in the context of trade. A wide range of evidence, from archeological to etymological, is utilized to demonstrate that relations between men and God, carried out through the intermediary of state-religious authorities, played a causal role in the genesis of the ox-unit of value and account, and, further, in the origins of money, and, subsequently, coinage. The substantive state-religious approach presented in this paper is also compared and contrasted to the Chartalist perspective on money's origins. It is concluded that the substantive approach presented in this paper differs from the more formal approaches (e.g., Metallism) because it does not rely upon a projection of modern institutions and habits of thought (e.g., a medium of exchange; monetary taxation) into ancient societies.
Keywords: ancient societies; money; substantive approach

The Polanyi-Stanfield Contribution: Reembedded Globalization - Brown, Doug (Forum for Social Economics, 2011)
This essay describes and interprets J. Ron Stanfield's analysis of Karl Polanyi. Stanfield has helped to clarify Polanyi's "double-movement" thesis by arguing that the double movement of self-regulating market forces and the protective response is essentially about freedom versus security. These insights provide an analysis that takes Polanyi into the twenty-first century by developing a theory of "reembedded globalization." This is not something that Polanyi experienced before his death in 1964. Corporate globalization and the escalation of free-market rhetoric have led to a new round of disembedding since the 1970s, and this is evident by both the top-down, corporate globalization of privatization, deregulation, and marketization, as well as, by the challenges to it from the "movement of movements" coalescing around the World Social Forum. The most conspicuous evidence of this neo-protective response and its challenge to corporate-driven market forces is that between the security needs of the world's globalization victims and the freedom of transnational corporations to make profits anywhere and in any way throughout the world. Understanding the clash in this way suggests that for humanity to save itself, it must struggle to reembed globalization and put security ahead of unbridled freedom. Reembedding globalization requires asserting democratic security ahead of the economic freedom of big business.
Keywords: MARX, Karl, 1818-1883; Marxian; Sraffian; capitalist systems; current heterodox approaches; globalization; history of economic thought; international economic order; political economy; reembedded; socialism

Economic Surplus, Social Reproduction, Nurturance and Love - O'Hara, Phillip Anthony (Forum for Social Economics, 2011)
This paper examines the contributions of James Ronald Stanfield to social and political economy. We start the analysis with Stanfield's contribution to institution building through his education of PhD students, building a graduate program in political economy, and through the associations of social and political economy. Then we go on to scrutinise his creative developments and applications of the notions of economic surplus and social reproduction. This is followed by his extensive work on Karl Polanyi and the disembedded economy. Finally we explore his path-breaking analysis of the great capitalist restoration, the nurturance gap and love. Stanfield was one of the greatest institutionalists and social economists of the last hundred years, and these four areas of energetic creativity are his prime achievements in the area.
Keywords: Marxian; Sraffian; current heterodox approaches: socialist; history of economic thought: individuals

Some Social Economics Concepts for Future Research - Stanfield, James Ronald (Forum for Social Economics, 2011)
Under the guidance of a recrudescent nineteenth century ideology, the governance of the global economy has been profoundly altered in the past three decades; indeed, a veritable Great Capitalist Restoration has emerged. It is important to view the transitioning economies and emerging market economies as part of this massive shift in governance. The concept of economic surplus offers a useful perspective on the political economy of governance regimes. Karl Polanyi's post-Marxian view of lives and livelihood provides important insight into the nature of the Great Capitalist Restoration, its ideologically-driven impetus, and its eventual foundering on the shoals of instability, insecurity, inequality, and social and ecological unsustainability. The ineluctable crisis of the Great Capitalist Restoration provides another opportunity to construct a viable democratic economic future, one that avoids the pitfalls that brought down the corporate-welfare state, and offers more than inauthentic, joyless commodity consumption. To build the Road to this Future, we will need a powerful heterodox economic analysis of agency and governance, guided by a vision of an economy which is subordinate to the lives it provisions.
Keywords: Marxian; Sraffian; capitalist systems: political economy; current heterodox approaches: socialist; international economic order; social economy

Understanding India’s New Political Economy: A Great Transformation? - Ruparelia, Sanjay; Reddy, Sanjay; Harriss, John; Corbridge, Stuart (Taylor & Francis, 2011)
A number of large-scale transformations have shaped the economy, polity and society of India over the past quarter century. This book provides a detailed account of three that are of particular importance: the advent of liberal economic reform, the ascendance of Hindu cultural nationalism, and the empowerment of historically subordinate classes through popular democratic mobilizations. Filling a gap in existing literature, the book goes beyond looking at the transformations in isolation, managing to: • Explain the empirical linkages between these three phenomena • Provide an account that integrates the insights of separate disciplinary perspectives • Explain their distinct but possibly related causes and the likely consequences of these central transformations taken together By seeking to explain the causal relationships between these central transformations through a coordinated conversation across different disciplines, the dynamics of India’s new political economy are captured. Chapters focus on the political, economic and social aspects of India in their current and historical context. The contributors use new empirical research to discuss how India’s multidimensional story of economic growth, social welfare and democratic deepening is likely to develop. This is an essential text for students and researchers of India's political economy and the growth economies of Asia.
Keywords: India; business & economics; ethnic studies

Karl Polanyi's Institutional Theory: Market Society and Its "Disembedded" Economy - Cangiani, Michele (Journal of Economic Issues, 2011)
A fundamental principle of Karl Polanyi's institutional outlook is that any economic system has to be considered as a whole and as a historically specific social organization. This principle implies a comparative method and a critique of conventional economics. Besides, the problem of the interrelation between the economic system and other aspects of social life cannot be avoided. On this basis, Polanyi points out the peculiar "economic" nature of the market-capitalist society and explains the institutional transformations characterizing its history. The opposition "embedded/disembedded," used by Polanyi to distinguish pre-modern economies from the market economy, has been widely adopted in recent times, particularly by economic sociologists, as a key for understanding current complex economic phenomena. However, the reference to Polanyi often presupposes a distorted interpretation of his theory, and a different kind of institutional approach.
Keywords: comparative economics; disembedded economy; economic policy; economic systems; embedded economy; institutional economics; institutional method

Adventures of an Austrian Trio Abroad: The Influence of Schumpeter, Polanyi and Hayek in Turkey and the Dissemination of Their Work - Ozveren, Eyup (The Dissemination of Economic Ideas, 2011)
Keywords: Austrian; Keynesian; Keynesianism; evolutionary; general aggregative models: Keynes; history of economic thought; history of economic thought since 1925: historical; history of economic thought: individuals; institutional; post-Keynesian; role of economics; role of economists